FENOMENOLOGI “SAYUR GANTUNG” MASYARAKAT BLITAR SEBAGAI UPAYA PENGURANGAN DAMPAK EKONOMI DI TENGAH COVID-19 - Diana Elvianita Martanti; Nanang Rudi Hartono; Sunarsasi Sunarsasi (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2021)
The purpose of this study was to understand and find out the motives and meanings of "Sayur Hanging" carried out by the people of Blitar. Then in the future, the results of this research are expected to provide an understanding of the motives and meanings of "Sayur Hanging" carried out by the people of Blitar. The research method uses a qualitative approach that produces descriptive data in the form of speech or writing and observable behavior from the subject itself. This type of research is qualitative phenomenological. The results of this study are the hanging vegetable phenomenon occurs in a number of areas in Blitar, namely Sananwetan Village and Bendogerit Village, as for the meaning of the hanging vegetable phenomenon from the analysis that the authors get from the interview and analysis process is the activity of hanging vegetables on a pole that almost resembles a clothesline. by a number of residents in an area with the aim of helping people in need.